Temperature stabilization based on passive cooling technology in the initial design of an eco-friendly mini greenhouse - Zulkarnain Zulkarnain; Nurfi Hikma; Ramy Fitrah Izzah; Nandita Devira (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2023)
Greenhouses become one of the buildings where the cultivation of plants. The concept of environmentally friendly greenhouses is included in the current model of urban agriculture. The design of the greenhouse building concept is environmentally friendly by utilizing passive cooling technology. Passive cooling technology is used in this design to balance the temperature and humidity of the greenhouse through natural energy flow. The purpose of the research and design of this building is to investigate the temperature differences inside and outside the greenhouse space. The results of this study know that passive cooling with and without water greatly affects the temperature in the room. Passive cooling without water will produce hot temperatures in the room compared to passive cooling using water.